The importance of Didactic Sequence (SD) in Environmental Education: an experience report at the Monsenhor Boson Full-Time Education Center (Research, Society and Development, 2020)
This paper aims to discuss Environmental Education (EE), in an interdisciplinary context, emphasizing its importance in building a more sustainable, healthy and responsible society, stimulating the student's environmental awareness and citizenship. The study was carried out with 50 students from two classes of 3rd year of High School, from the Full Time Education Center - CETI Monsenhor Boson, in Água Branca-PI. To this end, a Didactic Sequence (SD) was carried out, in six stages (pre-test application; sensitization classes; making crafts using recycled materials; preparing menus reusing food scraps; culmination of the works, and; application of the post- test). The results of the research showed that the works developed during DS provided significant learning, evidenced by the improvement in the number of correct answers in the post-test (86%), in relation to the pre-test (58%), as well as by conceptions and attitudes presented by the students. It was noticed the students' engagement in the realization of DS, allowing the reflection of the need to preserve the environment, possibly making them, more aware subjects about the importance of the environment, so that they can put into practice some acquired knowledge. Thus, the use of DS was important in the teaching of Environmental Education, for citizen awareness, since this must be a continuous process, and must be constantly addressed in the school environment.